Expressive Acts from Trauma in Violence Case Report: Forensic Linguistic - Fifi Safreni; Nuzwaty Nuzwaty; Efendi Barus; Purwanto Siwi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research aims to investigate messages that describe the expressive speech act of the traumatic feelings experienced by the victim, caused by violence as a result of hatred that turned into revenge originating from humiliation, discrimination, betrayal, and injustice. Mental violence was experienced by the main perpetrator Zuraida Hanum, which is reflected in expressive acts stemming from trauma due to continuously experiencing humiliation, being degraded, and betrayed by the victim judge Jamaluddin, who was her husband. Forensic Linguistics is applied to scientifically analyze language and law in messages and statements of violence case reports. The theory used is the expressive speech act from pragmatics concerning the trauma experienced by the victim, employing a psychoanalytic approach. In conducting this research. The method used by Creswell (2014) is a qualitative descriptive method with data collection procedures related to the research topic, from primary data sources of court decisions and secondary data from books, journals, and current news. Collecting information using Searle's speech act theory in Yule, namely: pain, like, dislike, sorrow, apologize from trauma using Sigmund Freud's theory of impersonate trauma, interpersonate trauma, and attached trauma will help readers understand the meaning of expressions comprehensively, namely expressive acts from traumatic experiences, as well as causal relationships explained in detail. The finding of expressive acts are included pain, like, dislike, sorrow, and apologize, and trauma from mental violence such as interpersonal trauma and attached trauma. The result shows that the expressive speech acts experienced by trauma victims are significant, including dislike and sorrow and interpersonal trauma from the perpetrator dominates the reporting of these violence cases.